Study guides

☆☆

Q: What is the answer to 2s - 3t equals 23 4s plus 3t equals 19?

Write your answer...

Submit

Still have questions?

Related questions

your answer is 1223

2s-2b= a+b+c-2b simplified that would be a+c-b.

s=4

It is the same as: 2s = t

2s - 12 + 2s = 4s - 124s - 12 = 4s - 124s = 4ss = s==========this is an identity and any number can be s

2s + s + 12 =132 ie 3s = 132 -12 3s = 120 s = 40

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)

2s + 16 = 4s - 6 Subtract 2s from both sides: 16 = 2s - 6 Add 6 to both sides: 22 = 2s divide both sides by 2: s = 11

It simplifies to: 2s+4R

2s + 17 = 2s + 17 1) First, you want to start on the left side of the equation and subtract 17 from both sides. 2s = 2s 2) Then, you take the 2 on the left side and divide it on both sides. s = s 3) You are left with s (Or 1s) on both sides, so s = 1.

First, add 19 on both sides. You end up with 2s = 48. Then divide both sides by 2 in order to isolate the 's'. You get s = 24.

If p = 2s + 5, then s = (p-5)/2 or 1/2 (p-5) --- p = 2s +5 p-5 = 2s (p-5)/2 = s

2s + s + 12 = 132 3s + 12 = 132 3s = 132 - 12 3s = 120 s = 40

21- only true legends know

Through a process of elimination and substitution the solutions are s = 8 and x = 5

The equivalent is 7s+2s = 9s

It is a simple linear equation in 's'. Its solution is the number that 's' must bein order to make it a true statement. The solution may be found like this:4s + 10 = 2s + 2Subtract 10 from each side of the equation:4s = 2s - 8Subtract 2s from each side:2s = -8Divide each side by 2 :s = -4

If you mean: -4+3+2s = 15 then s = 8

5 + 2s + s = 3s - s + 8 Combining like terms on the same side: 5 + 3s = 2s + 8 Subtracting 2s from both sides: 5 + s = 8 Subtracting 5 from both sides: s = 3

2r + 2s = 50 2r - s = 17 therefore 4r - 2s = 34 Add so that you can eliminate one of the variables: 2r + 2s = 50 4r - 2s = 34 ---------------- 6r + 0s = 84 Solve for r: 6r = 84 r = 14 Substitute r into one of the original equations: 2(14) + 2s = 50 28 + 2s = 50 2s = 22 s = 11 Doublecheck with the other original equation: 2(14) - 11 = 28 - 11 = 17

17

the correct answer would have to be 2molS+3molO2 -------->2SO3(g)

5s - 6 = 2s, ie 5s - 2s = 6, ie 3s = 6, ie s = 2

3q+4r-s+5q-6r+2s

2s-4 equals 2(s-2). You can find the answer by factoring two out of both numbers.